LITERATURE STUDY: CORRELATION NUTRITION STATUS WITH WOUND HEALING - Nova Mayasari; Oscar Indra Kusuma; Sianty Dewi (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Background: Perineal rupture is the most common complication of vaginal delivery. Similar to the wound healing process in general, the perineal wound healing process is influenced by nutritional factors. Nutritional factors that are known to be related to the wound healing process are protein levels which are reflected in albumin levels. In Indonesia, serum protein levels are not a variable that is routinely monitored in pregnant women. With a high prevalence of perineal wounds, measurement of serum albumin levels can be a means of early detection of maternal nutritional factors that can affect wound healing outcomes.Objective  of this study was to determine the relationship between serum albumin levels and the degree of post-salary perineal wound healingMethods: The study was originally a prospective analytic observational study with a cross-sectional design. In response to the pandemic, the research design was changed to a literature study by searching for scientific publications during the last 5 years in Pubmed, Google Scholar, Sciencedirect, Researchgate, and Mendeley with the keywords Perineum, wounds, postpartum, albumin, nutrition and exclusion for literature studies. is inaccessible PDF and Publication not in the last 10 years .Results: There were 10 literatures regarding wound healing and nutritional status of which 6 literatures were perineal wounds and 4 literatures were wounds related to malignancy. From the literature, it was concluded as many as 10 literatures showed that there was a relationship between nutritional status and wound healing.Conclusion: : After reviewing the ten literatures, it can be concluded that there is a relationship between nutritional status and wound healing in mothers with perineal wounds.Keywords: Perineum, wound, postpartum, albumin, nutrition